Performance Appraisal of Librarians by 360 Degree Feedback: the Case of Public librarians of Guilan Province, Iran - Abdolhossein Farajpahlou; Fatemeh Nooshinfard; Maryam Hassanzadeh (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2013)
Purpose: This research aimed at performance appraisal of public librarians in Guilan province, using 360 degree feedback approach. Method: The survey used a questionnaire devised for data collection in 4 formats, to assess librarians by 4 groups:  superiors, colleagues, themselves, and library users. The research population was the community of all 80 public librarians in Guilan Province, north of Iran..  From a pool of the available sources and documents, items were derived or created in accordance with views of some academics and experts who were selected as a Delphi Panel from a range of people known for their experience and/or expertise in library management. Findings: In regard with Moral-Value Index, self-evaluations were significantly different  from those of  superiors, colleagues and library users. As far as the Process Index was concerned, there was a significant difference between the users’ viewpoints and other three groups. In relation to Performance Index, as well as the general appraisal, no significant difference was observed among the viewpoints of the four evaluating groups. Originality/Value: This the first application of 360 degree feedback approaches in Iranian libraries.